The global Japanese restaurant : mobilities, imaginaries, and politics - Farrer, James (James C.); Wank, David L., 1957- (Food in Asia and the Pacific., 2023)
"With more than 120,000 Japanese restaurants around the world, Japanese cuisine has become truly global. Through the transnational culinary mobilities of migrant entrepreneurs, workers, ideas and capital, Japanese cuisine spread and adapted to international tastes. But this expansion is also entangled in culinary politics, ranging from authenticity claims and status competition among restaurateurs and consumers to societal racism, immigration policies, and soft power politics that have shaped the transmission and transformation of Japanese cuisine. Such politics has involved appropriation, oppression, but also cooperation across ethnic lines. Ultimately, the restaurant is a continually reinvented imaginary of Japan represented in concrete form to consumers by restaurateurs, cooks, and servers of varied nationalities and ethnicities who act as cultural intermediaries. The Global Japanese Restaurant: Mobilities, Imaginaries, and Politics uses an innovative global perspective and rich ethnographic data on six continents to fashion a comprehensive account of the creation and reception of the "global Japanese restaurant" in the modern world. Drawing heavily on untapped primary sources in multiple languages, this book centers on the stories of Japanese migrants in the first half of the twentieth century, and then on non-Japanese chefs and restaurateurs from Asia, Africa, Europe, Australasia, and the Americas whose mobilities, since the mid-1900s, who have been reshaping and spreading Japanese cuisine. The narrative covers a century and a half of transnational mobilities, global imaginaries, and culinary politics at different scales. It shifts the spotlight of Japanese culinary globalization from the "West" to refocus the story on Japan's East Asian neighbors and highlights the growing role of non-Japanese actors (chefs, restaurateurs, suppliers, corporations, service staff) since the 1980s. These essays explore restaurants as social spaces, creating a readable and compelling history that makes original contributions to Japan studies, food studies, and global studies. The transdisciplinary framework will be a pioneering model for combining fieldwork and archival research to analyze the complexities of culinary globalization"--